Hard coat film and method for producing the same, and hard coat film-joined woodgrain plate material

The hard coat film for wood grain plate materials addresses the issue of compromised natural wood texture and insufficient scratch resistance by using an ionizing radiation curable resin and fine particles with optimized film thickness and concentration, resulting in enhanced visibility and scratch resistance.

JP2025059833APending Publication Date: 2025-04-10NIPPON PAPER IND CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023170165
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing hard coat films for wood grain plate materials compromise the natural wood texture and lack sufficient scratch resistance when applied.

Method used

A hard coat film with a hard coat layer containing an ionizing radiation curable resin and fine particles with a particle diameter of 4.5 μm or less, where the film thickness and fine particle concentration are optimized to maintain the natural wood texture and enhance scratch resistance.

Benefits of technology

The hard coat film achieves a well-balanced visibility and scratch resistance, maintaining the natural wood texture while providing excellent protection against scratches when applied to wood grain plate materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059833000001
    Figure 2025059833000001
Patent Text Reader

Abstract

To provide a hard coat film which does not impair feeling of natural wood even when being joined to a woodgrain plate material.SOLUTION: A hard coat film has a hard coat layer containing an ionizing radiation curable resin provided on at least one surface on a base material. The hard coat layer contains fine particles, and has a fine particle diameter of 4.5 μm or less. The relation between film thickness (A) (μm) of the hard coat layer and concentration (B) (mass%) of the fine particles to a solid content of the hard coat layer is within the range of A-0.26×B+1.7≤0.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hard coat film suitable for hard coating the surface of wood grain board materials such as natural wood. [Background technology]

[0002] For example, the use of hard coat films to prevent scratches on the surfaces of household goods such as tables, desks, chairs, and chests of drawers made from processed natural wood has been considered, and when a hard coat film is applied to the surface of a wood grain board, there is a demand for a hard coat film that has good visibility and does not impair the texture of the natural wood of the board.

[0003] As an example of conventional technology, Patent Document 1 proposes an antiviral article having a decorative layer such as a wood grain pattern or a cured material layer on a substrate such as a film. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 7226635 Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, there is prior art hard coat technology that decorates the surface of an article with a wood grain pattern possessed by a decorative layer, but no hard coat film is known that, when laminated to the surface of a wood grain board, retains the natural wood texture of the board and also has good scratch resistance (surface hardness).

[0006] Therefore, the object of the present invention is, first, to provide a hard coat film that does not impair the texture of natural wood even when laminated to a wood grain board, i.e., that retains the texture, and has good scratch resistance (surface hardness), and, second, to provide a hard coat film-laminated wood grain board obtained by laminating such a hard coat film to a wood grain board. [Means for solving the problem]

[0007] In order to solve the above problems, the inventors have conducted intensive research focusing on a gloss level that does not impair the texture of natural wood but brings out its natural texture, and a surface hardness that improves scratch resistance, and have completed the present invention based on the various findings they have gained. That is, the present invention has the following configuration.

[0008] (First invention) The hard coat film has a hard coat layer containing an ionizing radiation curable resin provided on at least one surface of a substrate, the hard coat layer containing fine particles having a diameter of 4.5 μm or less, and the relationship between the film thickness (A) (μm) of the hard coat layer and the concentration (B) (mass %) of the fine particles relative to the solid content of the hard coat layer is in the range of A-0.26×B+1.7≦0.

[0009] (Second Invention) In the hard coat film according to the first aspect of the present invention, the thickness (A) of the hard coat layer is in the range of 1.7 μm or more and 3.4 μm or less. (Third Invention) In the hard coat film according to the first or second invention, the concentration (B) of the fine particles relative to the solid content of the hard coat layer is 50 mass % or less.

[0010] (Fourth Invention) The hard coat film according to the first or second aspect of the present invention is characterized in that the glossiness of the hard coat film is 18.0% or less. (Fifth Invention) The hard coat film according to the first or second aspect of the present invention is characterized in that the gloss of the hard coat film when applied to a wood grain board is 22.0% or less.

[0011] (Sixth Invention) The hard coat film according to the first or second aspect of the present invention is characterized in that the hard coat film has a total light transmittance of 88.0% or more.

[0012] (Seventh Invention) The hard coat film according to the first or second aspect of the present invention is characterized in that the hard coat layer further contains inorganic metal particles.

[0013] (8th invention) The hard coat film according to the first or second aspect of the present invention is characterized in that the substrate is a polyethylene terephthalate film.

[0014] (9th invention) This is a method for producing a hard coat film having a hard coat layer provided on at least one surface of a substrate, the method comprising: applying a coating material for a hard coat layer, which contains an ionizing radiation curable resin and fine particles, and the fine particles have a diameter of 4.5 μm or less, to at least one surface of the substrate; drying the coating material to form a hard coat coating layer; and then irradiating the coating with ionizing radiation, such that the relationship between the film thickness (A) (μm) of the hard coat layer obtained by the above-mentioned method and the concentration (B) (mass %) of the fine particles relative to the solid content of the hard coat layer is within the range of A-0.26×B+1.7≦0.

[0015] (10th invention) The hard-coat film is a hard-coat film having a hard-coat layer containing an ionizing radiation curable resin on at least one surface of a substrate, the hard-coat layer containing fine particles having a diameter of 4.5 μm or less, and the relationship between the film thickness (A) (μm) of the hard-coat layer and the concentration (B) (mass %) of the fine particles relative to the solid content of the hard-coat layer satisfies A-0.26×B+1.7≦0, which is characterized by being laminated to a wood-grain board.

[0016] (11th invention) A hard coat film-laminated wood grain board according to a tenth aspect of the present invention, characterized in that the gloss of the hard coat film is 22.0% or less. Effect of the Invention

[0017] According to the present invention, it is possible to provide a hard coat film that does not impair the texture of natural wood even when it is laminated to a wood grain board, that is, that maintains the texture and has good scratch resistance (surface hardness). Since the hard coat film of the present invention has a good balance between the desired visibility and scratch resistance, it can be suitably used as a hard coat film for preventing scratches on, for example, tables and desks made by processing natural wood. Furthermore, according to a hard-coat film-laminated wood grain board obtained by laminating such a hard-coat film to a wood grain board, the surface of the wood grain board can be protected by the hard-coat film to prevent scratches, etc., and the texture of the surface of the wood grain board is not impaired, and visibility is also good. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described in detail. In the present invention, unless otherwise specified, the expression "XX to △△" means "not less than XX and not more than △△."

[0019] <Hard coat film> The hard coat film of the present invention will be described below. The hard coat film of the present invention is a hard coat film comprising a substrate and a hard coat layer containing at least an ionizing radiation curable resin provided on at least one surface of the substrate.

[0020] The hard coat film of the present invention can be preferably applied to, for example, household goods such as tables, desks, chairs, chests of drawers, etc., made by processing natural wood including cypress, cedar, etc. Of course, the applications listed here are merely examples, and the applications are not limited to these.

[0021] The substrate to be coated of the hard coat film of the present invention is usually a film substrate.The film substrate used in the present invention is not particularly limited, and can be exemplified by acrylic resin, triacetyl cellulose, polyethylene terephthalate, cycloolefin polymer, polycarbonate, polyethylene naphthalate, polyethylene, polytrimethylene terephthalate, polypropylene, polybutylene terephthalate, polybutylene naphthalate, polystyrene, polymethyl methacrylate, polystyrene glycidyl methacrylate, aromatic polyimide, alicyclic polyimide, polyamideimide and mixtures thereof.Among these film substrates, polyester film, acrylic film, triacetyl cellulose, polyethylene terephthalate, polycarbonate are particularly suitable.Furthermore, from the viewpoint of toughness, it is preferable to use polyethylene terephthalate.

[0022] The thickness of the film substrate varies depending on the application and cannot be generally determined, but when the above-mentioned applications are taken into consideration, the thickness is preferably in the range of, for example, 10 to 1000 μm, and more preferably in the range of 20 μm to 300 μm.

[0023] Next, the hard coat layer will be described. The resin contained in the hard coat layer can be any resin that forms a coating, without any particular limitation. In particular, it is preferable to use an ionizing radiation curable resin, since it can impart surface hardness (scratch resistance) to the hard coat layer and can adjust the degree of crosslinking by the amount of exposure to ultraviolet light or the like, thereby enabling adjustment of the surface hardness of the hard coat layer.

[0024] The ionizing radiation curable resin used in the present invention is not particularly limited as long as it is a resin that is cured by irradiation with ultraviolet light (hereinafter abbreviated as "UV") or an electron beam (hereinafter abbreviated as "EB"), but in order to provide coating hardness and form a three-dimensional crosslinked structure in the hard coat layer, it is preferable to use a polyfunctional acrylate that is curable by UV or EB and has three or more (meth)acryloyloxy groups in one molecule. Specific examples of UV or EB curable polyfunctional acrylates include urethane acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane ethoxy triacrylate, glycerin propoxy triacrylate, ditrimethylolpropane tetraacrylate, etc. The polyfunctional acrylates may be used alone or in combination of two or more.

[0025] Furthermore, the ionizing radiation curable resin used in the present invention is preferably a polymer having a weight average molecular weight in the range of, for example, 700 to 3600, and preferably has a weight average molecular weight divided by the number of functional groups in the range of 50 to 1500. If the weight average molecular weight divided by the number of functional groups is less than 50, the hard coat film will curl toward the hard coat layer side, causing problems in the subsequent processing steps and poor processing suitability. If the weight average molecular weight divided by the number of functional groups is more than 1500, the hardness will be insufficient and this is not suitable.

[0026] In addition, when the ionizing radiation curable resin used in the present invention has a weight average molecular weight of less than 1500, the number of functional groups in one molecule is preferably 3 to less than 10. In addition, when the weight average molecular weight of the ionizing radiation curable resin is 1500 or more, the number of functional groups in one molecule is preferably 3 to 20. Within the above range, curling can be suppressed while suppressing the occurrence of cracks under high temperature conditions, and appropriate processing suitability can be maintained. For example, it is suitable for use as a scratch prevention film to be attached to the surface of wood grain board material.

[0027] In addition to the above-mentioned ionizing radiation curable resins, the resin contained in the hard coat layer may include thermoplastic resins such as polyethylene, polypropylene, polystyrene, polycarbonate, polyester, acrylic, styrene-acrylic, and cellulose, and thermosetting resins such as phenol resin, urea resin, unsaturated polyester, epoxy, and silicone resin, within a range that does not impair the hardness and scratch resistance of the hard coat layer.

[0028] In order to cure the ionizing radiation curable resin contained in the hard coat layer, the coating liquid for forming the hard coat layer (paint for the hard coat layer) can contain a known photopolymerization initiator. As such a photopolymerization initiator, acetophenones and benzophenones can be used.

[0029] In the present invention, it is a preferred embodiment that the hard coat layer contains fine particles. By containing fine particles in the hard coat layer, it is possible to obtain a hard coat film that does not impair the texture of natural wood even when it is attached to a wood grain board material. The material of the fine particles used in the present invention is not particularly limited, and may be, for example, inorganic fine particles such as silica or alumina, or organic fine particles such as acrylic resin.

[0030] In order to obtain a hard coat film that does not impair the texture of natural wood even when applied to such wood grain boards, the hard coat layer contains fine particles with a diameter of 4.5 μm or less in the present invention. Furthermore, it is important in the present invention that the relationship between the film thickness (A) (μm) of the hard coat layer and the concentration (B) (mass%) of the fine particles relative to the solid content of the hard coat layer satisfies the relational expression A-0.26×B+1.7≦0 (hereinafter sometimes simply referred to as the "relational expression of the present invention"). In the present invention, the particle size refers to the diameter of the particle. The diameter of the particle can be measured, for example, by cross-sectional analysis using an electron microscope (FlexSEM 1000 II, manufactured by Hitachi High-Technologies Corporation).

[0031] As described above, in the present invention, the particle diameter of the fine particles contained in the hard coat layer is 4.5 μm or less. If the particle diameter exceeds 4.5 μm, the surface texture of the film deteriorates, and the texture of natural wood is lost when the film is laminated to a wood grain board. There is no particular restriction on the lower limit of the particle diameter, but the particle diameter is 10 nm or more, preferably 100 nm or more, and more preferably 1 μm or more. If the particle diameter is too small, the antibacterial and antiviral properties may be inhibited even if an antibacterial and antiviral agent is added to the hard coat layer to impart antibacterial and antiviral properties to the hard coat layer.

[0032] The thickness (A) of the hard coat layer is not particularly limited as long as it satisfies the above-mentioned relational formula of the present invention, but is preferably in the range of, for example, 1.7 μm or more and 3.4 μm or less. If the thickness is less than 1.7 μm, it is difficult to obtain the necessary scratch resistance, which is not preferable. If the thickness exceeds 3.4 μm, the adhesion of the coating film decreases, which is not preferable. If the thickness exceeds 3.4 μm, the fine particles are buried in the hard coat layer, making it difficult to obtain the effects of the present invention. In the present invention, the thickness of the hard coat layer refers to the coating thickness of the hard coat layer after drying.

[0033] In addition, the concentration (B) of the fine particles relative to the solid content of the hard coat layer is not particularly limited as long as it satisfies the above-mentioned relational expression of the present invention, but is, for example, 50% by mass or less, preferably 40% by mass or less, and more preferably 30% by mass or less. If the fine particle concentration is too high, the transmittance of the hard coat film may decrease and the texture of natural wood may be lost. On the other hand, if the fine particle concentration is too low, it becomes difficult to obtain the effect of maintaining the texture of natural wood, so the fine particle concentration is preferably 10.0% by mass or more. In the present invention, unless otherwise specified, the term "solid content of the hard coat layer" refers to "solid content in a coating liquid for forming a hard coat layer (paint for a hard coat layer) for forming a hard coat layer." The solid content is, for example, solid content of resin, additives, etc.

[0034] In addition, a leveling agent (surface modifier) ​​can be used in the hard coat layer to improve application properties. For example, known leveling agents such as fluorine-based, acrylic-based, siloxane-based, and adducts or mixtures thereof can be used.

[0035] In order to impart antifouling properties to the hard coat film of the present invention, a fluorine-based or siloxane-based antifouling agent (such as a leveling agent or a surfactant) can be added to the hard coat layer. The amount of the antifouling agent added is not particularly limited, but is preferably 0.05% by mass to 2.0% by mass based on the resin solid content in the coating material for the hard coat layer.

[0036] In addition, for example, inorganic metal particles can be added to the hard coat layer in order to impart antibacterial and antiviral properties. The inorganic metal particles are substances formed by incorporating metal ions such as silver, molybdenum, copper, and zinc into an inorganic compound (inorganic material), or substances in which metal ions such as silver, molybdenum, copper, and zinc are supported on an inorganic compound (inorganic material). Specific examples of inorganic metal particles include inorganic antibacterial and antiviral agents such as antibacterial and antiviral zeolite, antibacterial and antiviral apatite, and antibacterial and antiviral zirconia, which are formed by incorporating at least one metal ion of silver, molybdenum, copper, zinc, and the like into inorganic compounds such as zeolite, apatite, and zirconia. In addition, compounds in which at least one metal ion of silver, molybdenum, copper, and zinc is supported on zeolite, apatite, zirconia, glass, and the like are also preferably exemplified. The amount of inorganic metal particles added is not particularly limited, but is preferably within the range of, for example, 0.05% by mass to 30% by mass relative to the solid content in the hard coat layer.

[0037] Other additives that may be added to the hard coat layer include antistatic agents, ultraviolet absorbers, antifoaming agents, surface tension regulators, antioxidants, light stabilizers, and the like, if necessary.

[0038] The hard coat layer can be formed as follows. In addition to the above-mentioned ionizing radiation curable resin and fine particles, the above-mentioned photopolymerization initiator, leveling agent, antifouling agent, and other additives, etc., are dissolved and dispersed in an appropriate solvent as necessary to form a coating liquid for forming a hard coat layer (paint for a hard coat layer). The coating liquid is applied onto the substrate to be coated, dried, and then irradiated with ionizing radiation such as UV or EB, whereby photopolymerization occurs to obtain a hard coat layer with excellent hardness.

[0039] The solvent can be appropriately selected depending on the solubility of the resin to be blended, and may be any solvent capable of uniformly dissolving or dispersing at least the solid content (resin, other additives, etc.) As such a solvent, for example, known organic solvents such as aromatic solvents such as toluene, xylene, and n-heptane, aliphatic solvents such as cyclohexane, methylcyclohexane, and ethylcyclohexane, ester solvents such as methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, and methyl lactate, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, and alcohol solvents such as methanol, ethanol, isopropyl alcohol, and n-propyl alcohol can be used alone or in combination.

[0040] Furthermore, the concentration (solid content concentration) of the coating liquid is not particularly limited, but can be, for example, in the range of about 10% by mass to 70% by mass.

[0041] The method for applying the coating solution for forming the hard coat layer is not particularly limited, and examples of the coating method include known coating methods such as gravure coating, microgravure coating, fountain bar coating, slide die coating, slot die coating, screen printing, and spray coating.

[0042] Furthermore, the drying temperature and heating time (drying time) in the drying step after coating can be appropriately set.

[0043] After the hard coat layer-forming coating liquid is applied to a substrate and dried, the amount of ionizing radiation (UV, EB, etc.) irradiated may be any amount necessary to impart sufficient hardness to the hard coat layer, and may be appropriately set depending on the type of ionizing radiation curable resin, etc.

[0044] The coating thickness (after drying) of the hard coat layer is as described above.

[0045] The hard coat film of the present invention is also characterized in that the surface of the hard coat layer is provided with hardness (scratch resistance).

[0046] Furthermore, the hard coat film of the present invention has a glossiness of 18.0% or less, and when laminated to a wood grain board material such as cypress or cedar, the glossiness is 22.0% or less, and further has a total light transmittance of 88.0% or more. It is presumed that the hard coat film of the present invention can be adjusted to a gloss level that does not impair the texture of natural wood even when the hard coat film is laminated to a wood grain board by adjusting the film thickness of the hard coat layer, the particle diameter of the particles contained in the hard coat layer, and the concentration of the particles relative to the solid content of the hard coat layer so as to fall within the range that satisfies the above-mentioned relational expressions of the present invention.

[0047] Thus, the hard coat film of the present invention has a sufficiently high total light transmittance, a glossiness of 18.0% or less, and a glossiness of 22.0% or less when laminated to a wood grain board, and most of its optical properties are external haze caused by external scattering of the hard coat layer. As a result, when the hard coat film is laminated to a wood grain board of natural wood such as cypress or cedar, a hard coat film that does not impair the texture of the natural wood board, that is, that maintains the texture and has good scratch resistance can be obtained. The hard coat film of the present invention thus has a good balance between the desired visibility and scratch resistance, and can be suitably used as a hard coat film for preventing scratches on tables and desks made of wood grain boards, for example.

[0048] The hard coat film of the present invention described above can be produced, for example, by a method for producing a hard coat film in which a hard coat layer is provided on at least one surface of a substrate, the method being characterized in that a coating material for a hard coat layer, which contains an ionizing radiation curable resin and fine particles, and the fine particles have a diameter of 4.5 μm or less, is applied to at least one surface of the substrate, and then dried to form a hard coat coating layer, and then irradiated with ionizing radiation to obtain a film thickness (A) (μm) of the hard coat layer, and a concentration (B) (mass %) of the fine particles relative to the solid content of the hard coat layer, satisfy the relationship A-0.26×B+1.7≦0.

[0049] As described above, the hard coat film of the present invention can be obtained without impairing the texture of natural wood even when it is laminated to a wood grain board, that is, the texture is maintained, and the hard coat film has good scratch resistance (surface hardness). Since the hard coat film of the present invention can obtain a good balance between the desired visibility and scratch resistance, it can be suitably used as a hard coat film for preventing scratches on, for example, tables and desks made by processing natural wood.

[0050] <Wood grain boards laminated with hard coat film> The hard coat film-laminated wood grain board of the present invention will be described below. The hard-coat film-laminated wood grain board of the present invention is characterized in that the hard-coat film is provided on at least one surface of a substrate with a hard-coat layer containing an ionizing radiation curable resin, the hard-coat layer contains fine particles, the fine particles having a diameter of 4.5 μm or less, and the relationship between the film thickness (A) (μm) of the hard-coat layer and the concentration (B) (mass %) of the fine particles relative to the solid content of the hard-coat layer is within the range of A-0.26×B+1.7≦0, and is laminated to the wood grain board.

[0051] The hard coat film-laminated wood grain board is formed by laminating the hard coat film of the present invention having the above-mentioned characteristics to a wood grain board, and the structural characteristics of the hard coat film in this case are as described above.

[0052] The hard coat film laminated wood grain board is also characterized in that the gloss of the hard coat film is 22.0% or less.

[0053] In the present invention, "wood grain board material" includes not only board materials made by processing natural wood, but also resin board materials having a decorative layer (printed layer) that shows the wood grain pattern such as annual rings and vessel grooves on the surface of a wooden board, and the like, and thus the surface is decorated with a wood grain pattern. In short, it includes all board materials having a natural wood grain pattern on the surface.

[0054] According to the hard-coat film laminated wood grain board of the present invention, which is obtained by laminating the above-mentioned hard-coat film to a wood grain board, the surface of the wood grain board can be protected by the hard-coat film to prevent scratches, and the texture of the surface of the wood grain board is not impaired, and good visibility can be obtained. The hard-coat film laminated wood grain board of the present invention can be used as a component material for various products, including wooden furniture products such as tables, desks, chairs, and chests, and their members or parts. EXAMPLES

[0055] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following description, "parts" means parts by mass unless otherwise specified, and "%" means % by mass unless otherwise specified.

[0056] <Example 1> A resin composition for forming a hard coat layer, which is composed of the following composition, was applied to one side of a substrate film (film thickness 50 μm) made of polyethylene terephthalate (PET) using a bar coater, and dried for 60 seconds in a drying oven at 80°C to form a hard coat layer with a film thickness (coating film thickness after drying) of 1.7 μm. This was then irradiated with UV light at a dose of 207 mJ / cm using a UV irradiation device set at a height of 60 mm from the coating surface. 2 The hard coat film of Example 1 was prepared by curing at 40° C. for 1 hour.

[0057] (Resin composition for forming hard coat layer) The resin composition was prepared by mixing 95 parts of an ionizing radiation curable resin (Shikoh UV-7630B (product name); manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) mainly composed of urethane acrylate, 3.5 parts of Irgacure 184 (photopolymerization initiator, manufactured by BASF), 1.5% (0.5% based on solids) of a surface modifier (Megafac R-08MH; manufactured by DIC Corporation), and 0.09% (0.3% based on solids) of an antibacterial and antiviral agent containing a silver-molybdenum compound as an inorganic metal. Fine particles (acrylic fine particles with a fine particle diameter of 4.5 μm (Techpolymer; manufactured by Sekisui Chemical Co., Ltd.)) were added so that the solids concentration was 14.0%, and the mixture was diluted with butyl acetate / n-propyl alcohol = 50 / 50 (parts by weight) to prepare a resin composition for forming a hard coat layer with a final solids concentration of 30%.

[0058] <Example 2> A hard coat film was produced in the same manner as in Example 1, except that the fine particle concentration (relative to solid content concentration) of the resin composition for forming a hard coat layer in Example 1 was changed to 20.0%, and the film thickness of the hard coat layer was changed to 3.4 μm.

[0059] <Example 3> A hard coat film was produced in the same manner as in Example 1, except that the fine particle concentration (relative to solid content concentration) of the resin composition for forming a hard coat layer in Example 1 was changed to 26.0%, and the film thickness of the hard coat layer was changed to 2.1 μm.

[0060] <Example 4> A hard coat film was produced in the same manner as in Example 1, except that the fine particle concentration (relative to solid content concentration) of the resin composition for forming a hard coat layer in Example 1 was changed to 26.0%, and the film thickness of the hard coat layer was changed to 3.4 μm.

[0061] <Comparative Example 1> A hard coat film was prepared in the same manner as in Example 1, except that the fine particle concentration (relative to solid content concentration) of the resin composition for forming a hard coat layer in Example 1 was changed to 10.0%, and the film thickness of the hard coat layer was changed to 2.5 μm.

[0062] <Comparative Example 2> A hard coat film was produced in the same manner as in Example 1, except that the fine particle concentration (relative to solid content concentration) of the resin composition for forming a hard coat layer in Example 1 was changed to 10.0%, and the film thickness of the hard coat layer was changed to 3.4 μm.

[0063] <Comparative Example 3> A hard coat film was prepared in the same manner as in Example 1, except that the fine particle concentration (relative to solid content concentration) of the resin composition for forming a hard coat layer in Example 1 was changed to 5.0%, and the film thickness of the hard coat layer was changed to 1.7 μm.

[0064] <Comparative Example 4> A hard coat film was produced in the same manner as in Example 1, except that the fine particle concentration (relative to solid content concentration) of the resin composition for forming a hard coat layer in Example 1 was changed to 46.0%, and the film thickness of the hard coat layer was changed to 10.5 μm.

[0065] <Evaluation> The hard coat films of the Examples and Comparative Examples prepared as described above were evaluated for the following items. The results are summarized in Table 1. The "thickness (A) of the hard coat layer (represented as "HC film thickness (A)" in the table)" and the "concentration of fine particles relative to the solid content of the hard coat layer (B)" in each of the above-mentioned Examples and Comparative Examples are also shown in Table 1. All of the hard coat films of Examples 1 to 4 satisfied the above-mentioned relational formula of the present invention. On the other hand, none of the hard coat films of Comparative Examples 1 to 4 satisfied the above-mentioned relational formula of the present invention.

[0066] <Coating thickness> The thickness of the coating film formed after drying of the hard coat layer (thickness of the hard coat layer) was measured using a Thin-Film Analyzer F20 (product name) (manufactured by FILMETRICS Co., Ltd.) In the present invention, the "thickness of the hard coat layer" refers to the value obtained by the above measurement.

[0067] <Glossiness> The glossiness of each hard coat film produced in the examples and comparative examples was measured using a gloss meter GM-3D manufactured by Murakami Color Research Laboratory Co., Ltd. The glossiness of each hard coat film when it was attached to a wood grain board made of cypress was also measured in the same manner. A glossiness of 18.0% or less was considered acceptable, and a glossiness of 22.0% or less when attached to a wood grain board was considered acceptable.

[0068] <Total light transmittance> Each hard coat film was measured using a haze meter HM-150N manufactured by Murakami Color Research Laboratory Co., Ltd. The measurements were carried out based on the standard JIS-K7361. The evaluation criteria were a total light transmittance of 88.0% or more was considered to be acceptable.

[0069] <Scratch resistance> For each of the hard coat films produced in the Examples and Comparative Examples, the hard coat layer surface was rubbed 10 times with steel wool #0000 under a load of 1 kg in a test method conforming to JIS-K-5600-5-10, and the degree of scratching was evaluated according to the following criteria: Products rated A and A' were deemed to have good scratch resistance. A: No scratches A': 1 to 10 scratches B: 11 to 20 scratches C: 21-30 scratches D: 31 or more scratches

[0070] [Table 1]

[0071] The hard coat films of the present invention Examples 1 to 4, which satisfy the relational expression of the present invention with respect to the relationship between the thickness of the hard coat layer and the concentration of the fine particles contained in the hard coat layer, are laminated to wood grain board and visually observed for texture, and all of the hard coat films have good visibility and do not impair the texture of natural wood.In addition, the hard coat films of the present invention Examples all have a glossiness of 18.0% or less, and when laminated to wood grain board material, the glossiness is 22.0% or less, but by adjusting the thickness of the hard coat layer, the fine particle diameter of the fine particles contained in the hard coat layer, and the fine particle concentration contained in the hard coat layer to be within the range satisfying the relational expression of the present invention, it is presumed that the hard coat film is adjusted to a low glossiness and high transmittance that does not impair the texture of natural wood even when laminated to wood grain board material. That is, according to the present invention, as is clear from Examples 1 to 4 shown in Table 1, a hard coat film having low gloss and high transmittance as well as excellent scratch resistance can be obtained.

[0072] Furthermore, the antibacterial properties of the hard coat films of the examples of the present invention were measured by a method conforming to the JIS Z 2801:2010 standard, and the result was an effective antibacterial activity value of 2.0 or more. Furthermore, the antiviral properties were measured by a method conforming to the ISO 21702:2019 standard, and the result was an effective antiviral activity value of 2.0 or more. In other words, the hard coat films of the examples of the present invention were also excellent in terms of antibacterial and antiviral properties.

[0073] The hard coat film of the present invention can be used as a component material for various products, including wooden furniture products such as tables, desks, chairs, chests of drawers, etc., and their members or parts. It can also be used as a surface protection film for these various products, and a surface protection film for the members or parts of various products. In another embodiment in which the hard coat film of the present invention is used as a component material for various products, their members or parts, it can be imparted with antibacterial and antiviral properties and used as an antibacterial and antiviral film.

[0074] On the other hand, when the hard coat films of Comparative Examples 1 to 4, which do not satisfy the relational expression of the present invention regarding the relationship between the film thickness of the hard coat layer and the concentration of fine particles contained in the hard coat layer, were attached to a wood grain board and visually observed for texture, all of the hard coat films lost the texture of natural wood and had poor visibility. The hard coat films of Comparative Examples 1 to 3 all had a glossiness higher than 18.0%, and the glossiness when attached to a wood grain board material was also higher than 22.0%. In addition, the hard coat film of Comparative Example 4 had a total light transmittance of less than 88.0%.

Claims

1. A hard coat film comprising a substrate and a hard coat layer containing an ionizing radiation curable resin on at least one surface of the substrate, the hard coat layer contains fine particles, and the fine particles have a diameter of 4.5 μm or less; A hard coat film, characterized in that the relationship between the thickness (A) (μm) of the hard coat layer and the concentration (B) (mass%) of the fine particles relative to the solid content of the hard coat layer is in the range of A-0.26×B+1.7≦0.

2. 2. The hard coat film according to claim 1, wherein the thickness (A) of the hard coat layer is in the range of 1.7 μm or more and 3.4 μm or less.

3. 3. The hard coat film according to claim 1, wherein a concentration (B) of the fine particles relative to the solid content of the hard coat layer is 50 mass % or less.

4. 3. The hard coat film according to claim 1, wherein the gloss of the hard coat film is 18.0% or less.

5. 3. The hard coat film according to claim 1, wherein the gloss of said hard coat film when applied to a wood grain board is 22.0% or less.

6. 3. The hard coat film according to claim 1, wherein the hard coat film has a total light transmittance of 88.0% or more.

7. 3. The hard coat film according to claim 1, wherein the hard coat layer further contains inorganic metal particles.

8. 3. The hard coat film according to claim 1, wherein the substrate is a polyethylene terephthalate film.

9. A method for producing a hard coat film having a hard coat layer provided on at least one surface of a substrate, comprising the steps of: A method for producing a hard coat film, comprising: applying a coating material for a hard coat layer, the coating material containing an ionizing radiation curable resin and fine particles, the fine particles having a diameter of 4.5 μm or less, to at least one surface of a substrate; drying the coating material to form a hard coat coating layer; and then irradiating the hard coat layer with ionizing radiation, the hard coat layer having a thickness (A) (μm) and a concentration (B) (mass %) of the fine particles relative to the solid content of the hard coat layer, the relationship being within the range of A-0.26×B+1.7≦0.

10. A hard-coat film comprising a hard-coat layer containing an ionizing radiation curable resin on at least one surface of a substrate, the hard-coat layer containing fine particles having a diameter of 4.5 μm or less, and a relationship between a film thickness (A) (μm) of the hard-coat layer and a concentration (B) (mass %) of the fine particles relative to the solid content of the hard-coat layer satisfying the following range: A-0.26×B+1.7≦0.

11. 11. The hard coat film-laminated wood grain board according to claim 10, wherein the gloss of the hard coat film is 22.0% or less.

Citation Information

Patent Citations

  • Antiviral article and antiviral resin composition

    JP7226635B2